Features of the ovulatory function restoration in women - O.V. Bulavenko; O.V. Furman; O.L. Ocheretna; V.V. Kelman (Репродуктивная эндокринология, 2021)
Myo-inositol is considered an additional insulin-sensitive supplement that may benefit women with polycystic ovary syndrome (PCOS). Correcting insulin resistance and lowering circulating insulin levels are key therapeutic options in the PCOS treatment, which in turn increase fertility and reduce the risk of type 2 diabetes and early cardiovascular diseases. Research objective: to determine the effectiveness of the Miofolic drug (contains myo-inositol 2000 mg, 5-methyltetrahydrofolate 200 μg, vitamin B12 2,5 μg) for the restoration of ovulatory dysfunction in women with PCOS phenotype A (ovulatory dysfunction + hyperandrogenism + polycystic ovarian structure). Materials and methods. The study included 60 women of reproductive age with PCOS phenotype A. 31 patients (group І) had normal weight, 29 patients (group ІІ) were overweight. Patients of both clinical groups received therapy with Miofolic 2 sachets for 6 months. Also, women in both groups were given recommendations for lifestyle modifications and a diet with limited carbohydrate content. Treatment efficacy was monitored after 3 and 6 months by determining body mass index, free testosterone index, 75 g glucose tolerance test, progesterone levels in the second phase of the menstrual cycle and ultrasound folliculometry. Results. In the first group, ovulatory cycles resumed after 3 months in 38.7% of patients (p < 0.05), and after 6 months in 58.06% (p < 0.01). In the second group, ovulatory cycles resumed after 3 months in 34.4% of women (p < 0.05), and after 6 months in 41.3% (p < 0.05). Conclusions. The results of this study allow us to recommend the Miofolic drug as the main method of inducing ovulation in women with PCOS with and without overweight, the period of the drug use is from 3 to 6 months. A more stable restoration of ovulatory function occurs after 6 months of therapy.